Badanie odczucia subiektywnego związanego z dzieleniem na sylaby wyrazów języka polskiego ― podział grup złożonych ze spółgłosek sonornych - Śledziński, Daniel (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
This paper presents the results of an investigation of subjective feelings related to the syllabification of Polish words written in orthographic form. The results presented are limited to consonant clusters that contain at least one sonorant. This is a continuation of the author’s previous paper: An investigation of subjective feelings related to syllabification in Polish — the division of consonant clusters composed of obstruents. In previous articles the author has shown that, despite the presence of numerous long consonant clusters in Polish, the process of syllabification may be based on phonological principles: the sonority principle and the principle of maximal onset. The main goal of the present investigations was to verify whether the syllabification based on phonology differs from that based on subjective feelings. The article also refers to some statistical properties of consonant clusters, with the aim of verifying whether the results presented here are related to those properties.